Didn't You Used to Be Somebody? - Kohler, Adrienne (Auckland University of Technology, 2019)
The screenplay, working title Didn’t You Used To Be Somebody?, is a creative exploration of sexism and ageism within the mainstream entertainment industry, and how this affects the perception of older women (defined as 35 years and older) in wider society. I developed the screenplay using a creative practice methodology that included dramaturgical analysis, traditional research into theories of feminism, and social construction theory. I also studied conventional screenwriting techniques such as the three-act structure, dramatic beats and character arcs. In this way, a screenplay was produced to offer a counter-story to the prevailing characterisation of ageing women in mainstream cinema. I also used a dramaturgical approach to trace and understand how cultural influences produced and continue to propagate these characterisations and how this influenced my creative process.
Keywords: Screenplay; Ageism; Women; Hollywood